Gutless - Deuker, Carl (Houghton Mifflin Harcourt, 2016)
"With both good speed and good hands, wide receiver Brock Ripley should be a natural for the varsity team, but he shies from physical contact. When his issues get him cut from varsity, he also loses his friendship with star quarterback Hunter Gates. Now a target for bullying, Brock struggles to overcome his fears and discover that, in his own way, he is brave enough"--